Systemic Risk and International Portfolio Choice - DAS, SANJIV RANJAN; UPPAL, RAMAN (Journal of Finance, 2004)
ABSTRACT Returns on international equities are characterized by jumps; moreover, these jumps tend to occur at the same time across countries leading to systemic risk . We capture these stylized facts using a multivariate system of jump‐diffusion processes where the arrival of jumps is simultaneous across assets. We then determine an investor's optimal portfolio for this model of returns. Systemic risk has two effects: One, it reduces the gains from diversification and two, it penalizes investors for holding levered positions. We find that the loss resulting from diminished diversification is small, while that from holding very highly levered positions is large.